Silicon-containing oxide-coated aluminum nitride particles

JP7652302B2Active Publication Date: 2025-03-27RESONAC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024002752
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-21
Filing Date
2024-01-11
Publication Date
2025-03-27
Estimated Expiration
2039-08-23

Smart Images

  • Figure 0007652302000011
    Figure 0007652302000011
  • Figure 0007652302000012
    Figure 0007652302000012
  • Figure 0007652302000013
    Figure 0007652302000013
Patent Text Reader

Abstract

To provide a method of producing an aluminum nitride particle coated with a silicon-containing oxide, capable of producing an aluminum nitride particle coated with a silicon-containing oxide maintaining high heat conductivity of the aluminum nitride particle and having improved moisture resistance, a method of producing a heat radiating resin composition containing aluminum nitride particles coated with a silicon-containing oxide, and an aluminum nitride particle coated with a silicon-containing oxide.SOLUTION: The method of producing an aluminum nitride particle coated with a silicon-containing oxide comprising an aluminum nitride particle and a silicon-containing oxide film that coats the surface of the aluminum nitride particle, includes a first step of coating the surface of an aluminum nitride particle with an organic silicone compound including a specific structure, and a second step of heating the aluminum nitride particle coated with an organic silicone compound at a temperature of 300°C or higher and lower than 1000°C, with the carbon atom content in the aluminum nitride particle coated with a silicon-containing oxide being less than 1000 mass.ppm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to aluminum nitride particles coated with silicon-containing oxide, a method for producing the same, and a method for producing a heat-dissipating resin composition containing the aluminum nitride particles coated with silicon-containing oxide. [Background technology]

[0002] Aluminum nitride has high thermal conductivity and excellent electrical insulation. Therefore, aluminum nitride is promising as a filler for resin compositions used in products such as heat dissipation sheets and sealing materials for electronic components. However, aluminum nitride undergoes hydrolysis when it reacts with moisture, and is transformed into aluminum hydroxide, which has low thermal conductivity. Furthermore, aluminum nitride generates ammonia, which is corrosive, during hydrolysis.

[0003] The hydrolysis of aluminum nitride also progresses due to moisture in the air. Therefore, products containing aluminum nitride may experience performance degradation under high temperature and humidity conditions, including reduced moisture resistance and thermal conductivity, as well as corrosion caused by ammonia produced by the hydrolysis of aluminum nitride.

[0004] Techniques proposed for improving the moisture resistance of aluminum nitride include a method of forming a layer made of Si-Al-ON on the surface of aluminum nitride powder (see, for example, Patent Document 1), a method of forming a coating layer on the surface of aluminum nitride powder using a silicate treating agent and a coupling agent (see, for example, Patent Document 2), a method of treating the surface of aluminum nitride powder with a silicate treating agent to leave organic groups on the surface of aluminum nitride powder (see, for example, Patent Document 3), and a method of surface-modifying the surfaces of aluminum nitride particles with a specific acidic phosphate ester (see, for example, Patent Document 4).

[0005] The moisture-proof aluminum nitride powder of Patent Document 1 is formed by applying a silicate ester layer to the surface of the aluminum nitride powder and then firing at a high temperature of 350 to 1000°C to form a layer made of Si-Al-ON on the surface. The aluminum nitride powder of Patent Document 2 is formed by performing a high-temperature heat treatment after surface treatment with a silicate treatment agent and a coupling agent to form a coating layer on the surface. The aluminum nitride powder of Patent Document 3 is improved in compatibility with resins by leaving organic groups by performing a heat treatment at a temperature not exceeding 90°C after surface treatment with a silicate treatment agent. The surface-modified particles of Patent Document 4 are improved in moisture resistance by aluminum nitride particles surface-modified with a specific acidic phosphate ester. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 3446053 [Patent Document 2] Patent No. 4088768 [Patent Document 3] Patent No. 4804023 [Patent Document 4] JP 2015-71730 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, the conventional techniques have the following problems. The above-mentioned aluminum nitride powder has a Si-Al-ON reaction layer, a coating layer formed by a silicate treatment agent and a coupling agent, a surface modification layer, etc., in order to improve moisture resistance. As a result, the moisture resistance is improved, but it is not yet at a sufficient level, and conversely, the coating used as a means to improve moisture resistance often reduces the thermal conductivity of the original aluminum nitride. Furthermore, there is a problem that it becomes difficult to mix it as a filler in various materials at a high filling rate.

[0008] The present invention has been made to solve the above-mentioned problems, and has an object to provide a method for producing aluminum nitride particles coated with silicon-containing oxide, which can produce aluminum nitride particles coated with silicon-containing oxide having improved moisture resistance while maintaining the high thermal conductivity of aluminum nitride particles, a method for producing a heat-dissipating resin composition containing aluminum nitride particles coated with silicon-containing oxide, and silicon-containing oxide-coated aluminum nitride particles. [Means for solving the problem]

[0009] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by coating aluminum nitride particles with a specific organosilicon compound by a specific method, and have completed the present invention. That is, the present invention has the following configuration.

[0010] [1] A method for producing aluminum nitride particles coated with a silicon-containing oxide, comprising: aluminum nitride particles; and a silicon-containing oxide coating covering the surfaces of the aluminum nitride particles, the method comprising the steps of: A first step of covering the surface of the aluminum nitride particles with an organosilicon compound having a structure represented by the following formula (1); A second step of heating the aluminum nitride particles covered with the organosilicon compound at a temperature of 300° C. or more and less than 1000° C., A method for producing aluminum nitride particles coated with a silicon-containing oxide, wherein the aluminum nitride particles coated with a silicon-containing oxide have a carbon atom content of less than 1000 ppm by mass. [ka] (In formula (1), R is an alkyl group having 4 or less carbon atoms.)

[0011] [2] The heating temperature in the second step is 300°C or higher and 800°C or lower; The method for producing aluminum nitride particles coated with a silicon-containing oxide according to [1], wherein the silicon-containing oxide coating is a silica coating, and the aluminum nitride particles coated with a silicon-containing oxide are silica-coated aluminum nitride particles.

[0012] [3] In the first step, the coating amount of the organosilicon compound is determined based on the specific surface area (m 2 / g) for surface area of ​​1 m 2 The method for producing aluminum nitride particles coated with silicon-containing oxide according to [1] or [2], wherein the amount of the aluminum nitride particles coated with silicon-containing oxide is 0.1 mg or more and 1.0 mg or less per unit area.

[0013] [4] The method for producing aluminum nitride particles coated with silicon-containing oxide according to any one of [1] to [3], wherein the first step is carried out by a dry mixing method or a gas phase adsorption method.

[0014] [5] The method for producing aluminum nitride particles coated with silicon-containing oxide according to any one of [1] to [4], wherein the first step is carried out in an atmosphere not containing oxygen gas.

[0015] [6] The method for producing aluminum nitride particles coated with silicon-containing oxide according to any one of [1] to [5], wherein the organosilicone compound having a structure represented by the formula (1) comprises at least one of a compound represented by the following formula (2) and a compound represented by the following formula (3): [ka] (In formula (2), R1 and R2 each independently represent a hydrogen atom or a methyl group, at least one of R1 and R2 represents a hydrogen atom, and m represents an integer of 0 to 10.) [ka] (In formula (3), n is an integer of 3 to 6.)

[0016] [7] The method for producing aluminum nitride particles coated with silicon-containing oxide according to any one of [1] to [6], wherein the first step is carried out under a temperature condition of 10° C. or higher and 200° C. or lower.

[0017] [8] A method for producing a heat dissipating resin composition, comprising a mixing step of mixing the aluminum nitride particles coated with silicon-containing oxide produced by the method for producing aluminum nitride particles coated with silicon-containing oxide according to any one of [1] to [7] with a resin.

[0018] [9] Silicon-containing oxide-coated aluminum nitride particles comprising aluminum nitride particles and a silicon-containing oxide coating covering the surfaces of the aluminum nitride particles, the silicon-containing oxide-coated aluminum nitride particles having a carbon atom content of less than 1000 ppm by mass and a Si / Al atomic ratio of 0.29 or more and 5.0 or less as measured by AES analysis of the surface.

[0019]

[10] The silicon-containing oxide coated aluminum nitride particles according to [9], wherein the Si / Al atomic ratio of the surface measured by AES analysis is 0.33 or more and 2.50 or less.

[0020]

[11] Silicon-containing oxide-coated aluminum nitride particles comprising aluminum nitride particles and a silicon-containing oxide coating covering the surfaces of the aluminum nitride particles, The carbon atom content is less than 1000 ppm by mass, The silicon-containing oxide coated aluminum nitride particles have a coverage of 15% or more and 100% or less by a silicon-containing oxide coating covering the surface of the aluminum nitride particles, as determined by LEIS analysis.

[0021]

[12] The silicon-containing oxide-coated aluminum nitride particles according to

[11] , wherein the coverage of the silicon-containing oxide coating covering the surface of the aluminum nitride particles is 25% or more and 40% or less as determined by LEIS analysis.

[0022]

[13] The silicon-containing oxide-coated aluminum nitride particles according to any one of [9] to

[12] , wherein the carbon atom content is 50 ppm by mass or more. Effect of the Invention

[0023] According to the present invention, it is possible to provide a method for producing silicon-containing oxide-coated aluminum nitride particles, which can produce silicon-containing oxide-coated aluminum nitride particles such as silica-coated aluminum nitride particles that maintain high thermal conductivity and have improved moisture resistance, a method for producing a heat-dissipating resin composition containing the silicon-containing oxide-coated aluminum nitride particles, and silicon-containing oxide-coated aluminum nitride particles. [Brief description of the drawings]

[0024] [Figure 1] 1 is a flowchart showing a method for producing silica-coated aluminum nitride particles of the present invention. [Diagram 2] FIG. 2 is a diagram showing the evaluation results of moisture resistance of particles of Examples and Comparative Examples. [Diagram 3] FIG. 2 is a diagram showing the evaluation results of the thermal conductivity of particles of Examples and Comparative Examples. [Figure 4] FIG. 1 is a graph showing the relationship between the moisture resistance of aluminum nitride particles coated with silicon-containing oxide and the Si / Al atomic ratio determined by AES analysis. [Diagram 5] FIG. 2 is a graph showing the relationship between the specific surface area of ​​aluminum nitride particles coated with silicon-containing oxide determined by a BET method and the silicon atom content of the aluminum nitride particles coated with silicon-containing oxide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be described in detail below.

[0026] <<Method for producing aluminum nitride particles coated with silicon-containing oxide>> The method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention produces aluminum nitride particles coated with silicon-containing oxide, which include aluminum nitride particles and a silicon-containing oxide coating covering the surface of the aluminum nitride particles. The "silicon-containing oxide" in the silicon-containing oxide coating or the aluminum nitride particles coated with silicon-containing oxide includes silica and composite oxides of silicon and aluminum, which will be described in detail later. Examples of the oxide include oxides, oxynitrides, oxycarbonitrides, etc. The method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention includes a first step of covering the surfaces of aluminum nitride particles with an organosilicon compound having a structure represented by the following formula (1), and a second step of heating the aluminum nitride particles coated with the organosilicon compound at a temperature of 300°C or higher and lower than 1000°C, preferably 300°C or higher and 800°C or lower, and the silicon-containing oxide coated aluminum nitride particles are characterized in that they have a carbon atom content of less than 1000 ppm by mass. [ka] (In formula (1), R is an alkyl group having 4 or less carbon atoms.)

[0027] Such a method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention will be described in detail with reference to Fig. 1. Fig. 1 is a flow chart showing a method for producing silica-coated aluminum nitride particles of the present invention, as an example of the method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention.

[0028] [Aluminum nitride particles] In the method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention, the aluminum nitride particles used as raw materials can be known ones such as commercial products. The method for producing aluminum nitride particles is not particularly limited, and includes, for example, a direct nitridation method in which metal aluminum powder is directly reacted with nitrogen or ammonia, and a reduction nitridation method in which alumina is carbon-reduced while being heated in a nitrogen or ammonia atmosphere to simultaneously carry out a nitridation reaction.

[0029] In addition, the aluminum nitride particles may be particles obtained by sintering aggregates of aluminum nitride fine particles into granules. In particular, sintered granules made from high-purity aluminum nitride fine particles having a cumulative volume d50 of about 1 μm can be suitably used as the aluminum nitride particles.

[0030] Here, the high-purity aluminum nitride fine particles refer to particles with a low oxygen content and a small amount of metal impurities. Specifically, for example, high-purity aluminum nitride with an oxygen content of 1 mass% or less and a total content of metal impurities (i.e., metal atoms other than aluminum) of 1000 mass ppm or less is suitable for obtaining higher thermal conductivity of the aluminum nitride particles contained in the silicon-containing oxide-coated aluminum nitride particles. The aluminum nitride particles can be used alone or in combination.

[0031] The oxygen content can be measured by an inorganic analyzer equipped with an infrared detector for oxygen detection. Specifically, the oxygen content can be measured by using an oxygen / nitrogen / hydrogen analyzer (ONH836: manufactured by LECO Japan LLC).

[0032] The total content of metal atoms other than aluminum can be measured using an ICP (Inductively Coupled Plasma) mass spectrometer, etc. Specifically, the total content of metal atoms other than aluminum can be measured using an ICP mass spectrometer (ICPMS-2030: manufactured by Shimadzu Corporation).

[0033] In this specification, the cumulative volume d50 of particles refers to the particle size at which the cumulative volume is 50% for a certain particle size distribution. The cumulative volume d50 is determined from the particle size distribution by the laser diffraction scattering method, and specifically, the cumulative volume d50 can be measured using a laser diffraction / scattering type particle size distribution analyzer (Microtrac MT3300EX2: manufactured by Microtrac BEL Co., Ltd.).

[0034] The shape of the aluminum nitride particles used in the present invention is not particularly limited, and examples thereof include amorphous (crushed), spherical, elliptical, plate-like (scale-like), etc. In addition, when the silicon-containing oxide-coated aluminum nitride particles are dispersed and contained in a heat-dissipating resin composition as a filler for a heat-dissipating material, the aluminum nitride particles may be only the same type of aluminum nitride particles (single particles) having the same shape and structure, but may also be used in the form of a mixture of aluminum nitride particles in which two or more different types of aluminum nitride particles having different shapes and structures are mixed in various ratios.

[0035] When the silicon-containing oxide-coated aluminum nitride particles are dispersed and contained in the heat-dissipating resin composition, the larger the volume ratio (filling amount) of the aluminum nitride particles constituting the silicon-containing oxide-coated aluminum nitride particles to the heat-dissipating resin composition, the higher the thermal conductivity of the heat-dissipating resin composition. Therefore, the shape of the aluminum nitride particles is preferably close to a sphere, which causes little increase in the viscosity of the heat-dissipating resin composition due to the addition of the silicon-containing oxide-coated aluminum nitride particles.

[0036] The average aspect ratio of aluminum nitride particles (index of particle shape) is preferably in the range of 0.8 to 1.0, more preferably in the range of 0.85 to 1.0, and even more preferably in the range of 0.9 to 1.0. Here, the average aspect ratio of aluminum nitride particles is the arithmetic mean value of the ratio (D1 / D2) of the minor axis (D1) and major axis (D2) of 100 randomly selected particles measured in an electron microscope photograph. The minor axis (D1) is the minimum length between two parallel lines in the electron microscope photograph of the aluminum nitride particle, and the major axis (D2) is the maximum length between two parallel lines in the electron microscope photograph.

[0037] The cumulative volume d50 of the aluminum nitride particles used in the present invention is preferably in the range of 0.2 μm or more and 200 μm or less, more preferably 10 μm or more and 100 μm or less, and further preferably 10 μm or more and 50 μm or less.

[0038] When the cumulative volume d50 of the aluminum nitride particles is within the above-mentioned range, even when a heat-dissipating resin composition containing aluminum nitride particles coated with a silicon-containing oxide is used in a heat-dissipating material for mounting power electronic components, it becomes possible to supply a thin heat-dissipating material with a minimum thickness, and the moisture resistance of the aluminum nitride particles is further improved, probably because the coating can easily uniformly cover the surface of the aluminum nitride particles.

[0039] In addition, since the method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention can form a thin coating layer of silicon-containing oxide, the effect on thermal conductivity is small even when relatively fine aluminum nitride particles with a cumulative volume d50 of 50 μm or less are used.

[0040] [Organosilicone compounds used for coating] In the method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention, the organosilicon compound used as the raw material for the silicon-containing oxide coating constituting the aluminum nitride particles coated with silicon-containing oxide can be any organosilicon compound containing the structure represented by the above formula (1), regardless of whether it is linear, cyclic or branched. The structure represented by formula (1) is a hydrogensiloxane unit in which hydrogen is directly bonded to a silicon atom.

[0041] In the above formula (1), R, which is an alkyl group having 4 or less carbon atoms, is preferably a methyl group, an ethyl group, a propyl group, a t-butyl group, etc., and is particularly preferably a methyl group. In the method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention, the organosilicon compound used as a raw material is, for example, an oligomer or polymer containing a structure represented by formula (1).

[0042] As the organosilicone compound, for example, at least one of a compound represented by the following formula (2) and a compound represented by the following formula (3) is preferable. [ka] (In formula (2), R1 and R2 each independently represent a hydrogen atom or a methyl group, at least one of R1 and R2 represents a hydrogen atom, and m represents an integer of 0 to 10.) [ka] (In formula (3), n is an integer of 3 to 6.)

[0043] In particular, the cyclic hydrogen siloxane oligomer in which n is 4 in the above formula (3) is excellent in that it can form a uniform coating on the surface of aluminum nitride particles. The weight average molecular weight of the organosilicone compound containing the structure shown in formula (1) is preferably 100 to 2000, more preferably 150 to 1000, and even more preferably 180 to 500. It is presumed that by using an organosilicone compound containing the structure shown in formula (1) with a weight average molecular weight in this range, it is easy to form a thin and uniform coating on the surface of aluminum nitride particles. In addition, in formula (2), m is preferably 1.

[0044] In this specification, the weight average molecular weight is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC), and specifically, the weight average molecular weight can be measured by using a column (Shodex (registered trademark) LF-804, manufactured by Showa Denko K.K.) in combination with a differential refractive index detector (Shodex (registered trademark) RI-71S, manufactured by Showa Denko K.K.).

[0045] <1st process> In the first step, the surfaces of the aluminum nitride particles are covered with an organosilicone compound containing the structure represented by the formula (1) above. In the first step, the method is not particularly limited as long as the surface of the aluminum nitride particles can be covered with an organic silicone compound containing the structure represented by formula (1). The method of the first step includes a dry mixing method in which an organic silicone compound is added by spraying or the like while stirring the raw aluminum nitride particles using a general powder mixing device, and then dry-mixed to coat the aluminum nitride particles. Examples of the powder mixing device include a Henschel mixer, a container-rotating V blender, a double cone blender, a ribbon blender having a mixing blade, a screw blender, a closed rotary kiln, and stirring with a stirrer in a closed container using a magnetic coupling. The temperature condition in this case is not particularly limited depending on the boiling point and vapor pressure of the silicone compound containing the structure represented by formula (1), but is preferably 10°C or higher and 200°C or lower, more preferably 20°C or higher and 150°C or lower, and even more preferably 40°C or higher and 100°C or lower.

[0046] As a method for the first step, a gas-phase adsorption method can be used in which the vapor of an organosilicon compound containing the structure represented by formula (1) alone or a mixed gas with an inert gas such as nitrogen gas is attached or deposited on the surface of aluminum nitride particles placed at rest. The temperature conditions in this case are not particularly limited depending on the boiling point and vapor pressure of the silicone compound containing the structure represented by formula (1), but a preferred temperature is 10°C to 200°C, more preferably 20°C to 150°C, and even more preferably 40°C to 100°C. If necessary, the system can be pressurized or depressurized. As an apparatus that can be used in this case, a closed system and an apparatus that can easily replace the gas in the system are preferred, and for example, a glass container, a desiccator, a CVD apparatus, etc. can be used. When the aluminum nitride particles are coated with the organosilicon compound without stirring, the treatment time needs to be longer. However, by intermittently placing the treatment container on a vibrator, it is possible to efficiently treat areas where the powders are in contact with each other and are in the shade, or powders far from the air layer above, by moving the position.

[0047] The amount of the organosilicon compound containing the structure represented by formula (1) used in the first step is not particularly limited. In the aluminum nitride particles covered with the organosilicon compound containing the structure represented by formula (1) obtained in the first step, the amount of the coating of the organosilicon compound containing the structure represented by formula (1) is determined based on the specific surface area (m2) of the aluminum nitride particles determined by the BET method. 2 / g) for surface area of ​​1 m 2 The specific surface area (m2) of the aluminum nitride particles coated with silicon-containing oxide is preferably 0.1 mg or more and 1.0 mg or less, more preferably 0.2 mg or more and 0.8 mg or less, and even more preferably 0.3 mg or more and 0.6 mg or less. The reason for this is that by making the specific surface area 0.1 mg or more, a uniform silicon-containing oxide coating with a large amount of coating can be formed in the aluminum nitride particles coated with silicon-containing oxide obtained through the second step described later in detail, and by making the specific surface area 1.0 mg or less, a thin silicon-containing oxide coating that does not reduce the thermal conductivity of the resulting aluminum nitride particles coated with silicon-containing oxide can be formed. Note that the specific surface area (m2) of the aluminum nitride particles obtained by the BET method is 0.1 mg or more, and 0.2 mg or more and 0.8 mg or less are more preferably 0.3 mg or more and 0.6 mg or less. The ...6 mg or less are more preferably 0.1 mg or more and 0.6 mg or less. 2 / g) for surface area of ​​1 m 2 The coating amount of the organosilicon compound containing the structure represented by formula (1) per aluminum nitride particle was calculated by multiplying the mass difference of the aluminum nitride particles before and after coating with the organosilicon compound by the specific surface area (m2) of the aluminum nitride particles determined by the BET method. 2 Surface area (m2) calculated from 2 ) can be calculated by dividing it by

[0048] The specific surface area determined by the BET method can be measured by a nitrogen adsorption BET one-point method using a gas flow method. As an evaluation device, Macsorb HM model-1210 manufactured by Mountech can be used.

[0049] <Second process> In the second step, the aluminum nitride particles covered with the organosilicon compound obtained in the first step are heated at a temperature of 300° C. or more and less than 1000° C., preferably 300° C. or more and 950° C. or less, more preferably 300° C. or more and 800° C. or less. This allows a silicon-containing oxide coating to be formed on the surface of the aluminum nitride particles. When the heating temperature in the second step is low, a silica coating is formed as a silicon-containing oxide coating on the surface of the aluminum nitride particles, and silica-coated aluminum nitride particles can be produced. When the heating temperature in the second step is high, a coating of a complex oxide of silicon and aluminum is formed as a silicon-containing oxide coating on the surface of the aluminum nitride particles, and aluminum nitride particles coated with a complex oxide of silicon and aluminum can be produced. It is presumed that when the temperature in the second step is high, the aluminum constituting the aluminum nitride particles comes out to the surface of the aluminum nitride particles to form a complex oxide together with the silicon derived from the organosilicon compound, and a coating of a complex oxide of silicon and aluminum is formed. In the second step, a general heating furnace can be used as long as it can heat the aluminum nitride particles covered with the organosilicone compound obtained in the first step at a temperature of 300°C or higher and lower than 1000°C, preferably 300°C or higher and 950°C or lower, and more preferably 300°C or higher and 800°C or lower, that is, as long as it can maintain the aluminum nitride particles covered with the organosilicone compound obtained in the first step in a temperature range of 300°C or higher and lower than 1000°C, preferably 300°C or higher and 950°C or lower, and more preferably 300°C or higher and 800°C or lower.

[0050] In the heat treatment of the second step (heating at a temperature of 300°C or more and less than 1000°C, preferably 300°C or more and 950°C or less, more preferably 300°C or more and 800°C or less), the organosilicon compounds containing the structure represented by formula (1) that coat the aluminum nitride particle surface in the early stage of the heat treatment are bonded to each other or to hydroxyl groups on the aluminum nitride particle surface by dehydrogenation reaction, which is thought to further strengthen the coating. Then, in the final stage of the heat treatment, the organic groups (alkyl groups having 4 or less carbon atoms) of the organosilicon compounds are decomposed and volatilized. Therefore, the silicon-containing oxide coating formed has a low carbon atom content, and the silicon-containing oxide-coated aluminum nitride particles also have a low carbon atom content. Therefore, it is possible to obtain silicon-containing oxide-coated aluminum nitride particles with a carbon atom content of less than 1000 ppm by mass. If the carbon atom content of the silicon-containing oxide-coated aluminum nitride particles is less than 1000 ppm by mass, the moisture resistance is good, and unevenly distributed carbon particles are less likely to affect the insulation properties. The carbon atom content of the aluminum nitride particles coated with silicon-containing oxide is preferably less than 500 ppm by mass, and more preferably less than 300 ppm by mass.

[0051] Incidentally, silica coating means that the material is coated with a thin film whose main component is silica. However, since there may be multiple inorganic compounds at the interface between the coated silica and the aluminum nitride particle, when analyzing with ToF-SIMS (Time of Flight Secondary Ion Mass Spectrometry, ION-TOF, TOF.SIMS5), recombination of secondary ions and decomposition during ionization may overlap, and segments such as AlSiO4 ions and SiNO ions may be detected as secondary components at the same time. The composite segments analyzed by this ToF-SIMS analysis can also be defined as partial detections when aluminum nitride is silicaized. As a guideline, if the amount of secondary electrons of silica is greater than the other fractions, silica can be considered to be the main component.

[0052] As an experiment to confirm the purity of silica with further accuracy, a sample surface in which a silica film was formed on an aluminum nitride polycrystalline substrate in the same manner was measured with a photoelectron spectroscopy device (XPS: X-ray Photoelectron Spectroscopy, ULVAC-PHI, Inc., Quantera II). The kinetic energy of the detected Si-derived photoelectrons was almost identical to the standard peak of silica, 103.7 eV, so it is presumed that most of the silica has a SiO2 structure. Depending on the heating temperature, organic components may remain. As long as the effect of the present invention is not impaired, it is quite possible that organic siloxane components are mixed in.

[0053] The carbon atom content can be measured using a carbon-sulfur analyzer that uses a non-dispersive infrared absorption method using a tubular electric furnace. Specifically, it can be measured using a carbon-sulfur analyzer (Carbon Anlyzer EMIA-821: manufactured by Horiba, Ltd.).

[0054] The heating temperature (heat treatment temperature) in the second step is 300°C or more and less than 1000°C, preferably 300°C or more and less than 950°C, more preferably 300°C or more and less than 800°C. By performing the process within this temperature range, a silicon-containing oxide film having good moisture resistance and thermal conductivity is formed. Specifically, when the film is heated at 300°C or more, the silicon-containing oxide film becomes dense and less permeable to moisture, so that the moisture resistance is good. Furthermore, when the film is heated at less than 1000°C, preferably 950°C or less, more preferably 800°C or less, the thermal conductivity is good. On the other hand, when the film is heated at 1000°C or more, the moisture resistance and thermal conductivity are deteriorated. Furthermore, when the heating temperature is 300°C or more and less than 1000°C, preferably 300°C or more and less than 950°C, more preferably 300°C or more and less than 800°C, a silicon-containing oxide film is formed uniformly on the surface of the aluminum nitride particles. Furthermore, if the heating temperature is 300° C. or higher, the silicon-containing oxide coating will have excellent insulating properties, and if the heating temperature is less than 1000° C., preferably 950° C. or lower, and more preferably 800° C. or lower, it is effective in terms of energy costs. The heating temperature is preferably 400° C. or higher, more preferably 500° C. or higher, and even more preferably 650° C. or higher.

[0055] The heating time is preferably 30 minutes to 12 hours, more preferably 30 minutes to 6 hours, and even more preferably 45 minutes to 4 hours. A heat treatment time of 30 minutes or more is preferable because no decomposition products of the organic group (alkyl group having 4 or less carbon atoms) of the organosilicon compound remain, and a silicon-containing oxide coating with a very low carbon atom content is obtained on the surface of the aluminum nitride particles. In addition, a heating time of 6 hours or less is preferable because silicon-containing oxide-coated aluminum nitride particles can be produced efficiently.

[0056] The atmosphere for the heat treatment in the second step is not particularly limited, and may be, for example, an inert gas atmosphere such as N2, Ar, or He, or an atmosphere containing a reducing gas such as H2, CO, or CH4. However, it is preferable to perform the heat treatment in an atmosphere containing oxygen gas, for example, in the atmosphere (air).

[0057] After the heat treatment in the second step, the aluminum nitride particles coated with silicon-containing oxide may be partially fused together. In that case, by crushing the aluminum nitride particles, aluminum nitride particles coated with silicon-containing oxide that are not stuck or aggregated can be obtained. The device used for crushing is not particularly limited, but a general crusher such as a roller mill, a hammer mill, a jet mill, or a ball mill can be used.

[0058] Furthermore, after the second step is completed, the first step and the second step may be carried out in sequence. That is, the step of carrying out the first step and the second step in sequence may be repeated.

[0059] When the surface of the aluminum nitride particles is covered with an organic silicone compound by a gas-phase adsorption method in the first step, the gas-phase adsorption method is capable of forming a uniform and thin silicon-containing oxide film compared to a liquid treatment method. Therefore, even if the first step and the second step are sequentially performed multiple times, for example, 2 to 5 times, the aluminum nitride particles can exhibit good thermal conductivity.

[0060] On the other hand, regarding moisture resistance, a positive correlation is observed between the number of steps of sequentially performing the first step and the second step and the moisture resistance. Therefore, the number of steps of sequentially performing the first step and the second step can be freely selected according to the level of moisture resistance required for practical applications.

[0061] The silicon-containing oxide-coated aluminum nitride particles obtained by the method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention described above maintain the high thermal conductivity inherent to aluminum nitride particles and also have excellent moisture resistance, and therefore can be widely used as a filler for heat dissipation materials used in the electrical and electronic fields, etc.

[0062] <<Silicon-containing oxide coated aluminum nitride particles>> The method for producing the silicon-containing oxide-coated aluminum nitride particles of the present invention can provide the silicon-containing oxide-coated aluminum nitride particles of the present invention, that is, the silicon-containing oxide-coated aluminum nitride particles comprising aluminum nitride particles and a silicon-containing oxide coating covering the surface of the aluminum nitride particles, and having a carbon atom content of less than 1000 mass ppm. The "silicon-containing oxide" of the silicon-containing oxide coating or the silicon-containing oxide-coated aluminum nitride particles includes the above-mentioned silica and a composite oxide of silicon and aluminum. The oxide includes oxides, oxynitrides, oxycarbonitrides, etc.

[0063] Such aluminum nitride particles coated with silicon-containing oxide according to the present invention maintain the high thermal conductivity of aluminum nitride particles and have excellent moisture resistance, as will be shown in the examples described later. For example, when the aluminum nitride particles coated with silicon-containing oxide of the present invention are put into a hydrochloric acid aqueous solution adjusted to pH 4 and treated at 85 ° C for 2 hours (i.e., the aluminum nitride particles coated with silicon-containing oxide are immersed in a hydrochloric acid aqueous solution adjusted to pH 4 at 85 ° C for 2 hours), the concentration of ammonia extracted in the hydrochloric acid aqueous solution can be 20 mg / L or less, and the moisture resistance is extremely excellent. In addition, since the hydrolysis reaction is promoted in an acidic solution more than in air, an accelerated moisture resistance test can be performed by exposing the particles to a hydrochloric acid aqueous solution adjusted to pH 4. Therefore, the moisture resistance of the aluminum nitride particles coated with silicon-containing oxide can be evaluated by using a hydrochloric acid aqueous solution of pH 4, and if the concentration of the ammonia is 20 mg / L or less, it can be said that the moisture resistance is good. In addition, by using a hydrochloric acid aqueous solution of pH 4, chemical resistance can also be compared. The concentration of the extracted ammonia is preferably 10 mg / L or less, and more preferably 6 mg / L or less. From the viewpoint of moisture resistance, the lower the carbon atom content, the better. Here, in the manufacturing method of the aluminum nitride particles coated with silicon-containing oxide of the present invention, the organic silicone compound having the structure represented by formula (1) is used as a raw material, so the aluminum nitride particles coated with silicon-containing oxide often contain carbon atoms, for example, 50 mass ppm or more, or even 60 mass ppm or more. However, as described above, if it is less than 1000 mass ppm, moisture resistance is excellent.

[0064] In addition, the aluminum nitride particles coated with silicon-containing oxide of the present invention preferably have an oxygen atom content of 1.60 mass% or less. When the oxygen atom content is 1.60 mass% or less, the thermal conductivity is more excellent. The oxygen atom content of the aluminum nitride particles coated with silicon-containing oxide is more preferably 1.5 mass% or less. In addition, the oxygen atom content of the aluminum nitride particles coated with silicon-containing oxide is preferably 0.01 mass% or more.

[0065] The coverage of the silicon-containing oxide film (SiO2) that covers the surface of an aluminum nitride particle by LEIS analysis can be calculated using the following formula. (S Al(AlN)-S Al (AlN+SiO2)) / S Al (AlN) x 100(%) In the above formula, S Al (AlN) is the area of ​​the Al peak of the aluminum nitride particle, and S Al (AlN+SiO2) is the area of ​​the Al peak of aluminum nitride particles coated with silicon-containing oxide. The area of ​​the Al peak can be obtained from analysis by low energy ion scattering (LEIS), a measurement method that uses an ion source and rare gas as a probe. LEIS is an analysis method that uses rare gas of several keV as incident ions, and is an evaluation method that enables composition analysis of the outermost surface (Reference: The TRC News 201610-04 (October 2016)).

[0066] In addition, in the case of the aluminum nitride particles coated with silicon-containing oxide of the present invention, the firing temperature in the second step described below is set to 650°C. In Table 1, the coverage of the silicon-containing oxide coating covering the surface of the aluminum nitride particles by LEIS analysis is, for example, 15% to 100%, preferably 70% to 100%, more preferably 95%, even more preferably 72% to 90%, and particularly preferably 74% to 85%. When it is 70% to 100%, the moisture resistance is more excellent. In addition, it was found that when it exceeds 95%, the thermal conductivity may decrease. Furthermore, when the firing temperature in the second step was examined, it was found that the balance between the thermal conductivity and the moisture resistance was unexpectedly improved at a higher firing temperature, as shown in Table 4 described below. In other words, when the firing temperature is increased, the thermal conductivity of Example 11 to Example 16 is higher than that of the second step of Table 1, which was fired at 650°C. More surprisingly, the coverage value of this Example by the LEIS analysis is found to be reduced to about 30% or less, even though the silicon content is almost the same as that of the second step of Table 1, which was fired at 650°C (Examples 3, 5, and 6). Since the principle of LEIS measurement reflects the analytical value of the elements in one surface layer, it is presumed that the silicon-containing oxide covering the surface of the aluminum nitride particles in Table 1, which was fired at 650°C, and the silicon-containing oxide covering the surface of the aluminum nitride particles in Table 4, which were fired at a high temperature, have changed crystal structures and chemical structures. It is presumed that the silicon-containing oxide-coated aluminum nitride particles, such as the silica-coated aluminum nitride particles of the present invention, also contain silica and other oxides of silicon atoms whose chemical structures have been changed by firing, complex oxides with other elements, etc., on the surface. Therefore, the coverage of silicon-containing oxide-coated aluminum nitride particles such as silica-coated aluminum nitride particles by the above LEIS analysis is preferably 15% or more, more preferably 20% or more, even more preferably 25% or more, and even more preferably 30% or more. If it is 15% or more, the moisture resistance is excellent. Also, it is preferably 100% or less, more preferably 95% or less, even more preferably 90% or less, and even more preferably 85% or less. If it is 100% or less, the thermal conductivity is excellent.The combination is preferably 15% or more and 100% or less, more preferably 15% or more and 90% or less, even more preferably 15% or more and 45% or less, even more preferably 25% or more and 45% or less, and most preferably 30% or more and 40% or less.

[0067] In addition, the silicon-containing oxide-coated aluminum nitride particles of the present invention have a specific surface area of ​​x (m 2 / g) and the silicon atom content of the aluminum nitride particles coated with silicon-containing oxide is y (ppm by mass), it is preferable to satisfy the following formulas (4) and (5), and it is more preferable to satisfy the following formula (6). y≦1000x+500 (4) y≧100 (5) 0.03≦x≦5 (6)

[0068] The silicon atom content can be measured by ICP method. The specific surface area x of the aluminum nitride particles coated with silicon-containing oxide determined by BET method can be measured by nitrogen adsorption BET one-point method by gas flow method, similarly to the specific surface area of ​​the aluminum nitride particles determined by BET method. Macsorb HM model-1210 manufactured by Mountech can be used as the evaluation device.

[0069] The silicon atom content of the aluminum nitride particles coated with silicon-containing oxide of the present invention is not particularly limited, but is, for example, 5000 mass ppm or less, preferably 3000 mass ppm or less, more preferably 2800 mass ppm or less, and even more preferably 2600 mass ppm or less. The silicon atom content of the aluminum nitride particles coated with silicon-containing oxide is, for example, 100 mass ppm or more.

[0070] In addition, the silicon-containing oxide-coated aluminum nitride particles of the present invention have a Si / Al atomic ratio of 0.29 or more, preferably 0.30 or more, and more preferably 0.32 or more, measured by AES (Auger Electron Spectroscopy) analysis of the surface. Thus, when the Si / Al atomic ratio measured by AES analysis is 0.29 or more, the moisture resistance is excellent. The upper limit of the Si / Al atomic ratio measured by AES analysis of the surface of the silicon-containing oxide-coated aluminum nitride particles is not particularly limited, but is, for example, 5.0 or less.

[0071] The Si / Al atomic ratio of the silicon-containing oxide-coated aluminum nitride particles, which is measured by AES analysis of the surface, can be measured using an Auger electron spectrometer (ULVAC-PHI, PHI-680).

[0072] <<Method for producing heat dissipating resin composition>> A heat dissipating resin composition can be produced using the silicon-containing oxide-coated aluminum nitride particles of the present invention. That is, the method for producing a heat dissipating resin composition of the present invention includes a mixing step of mixing the silicon-containing oxide-coated aluminum nitride particles produced by the method for producing the silicon-containing oxide-coated aluminum nitride particles with a resin. Examples of the "silicon-containing oxide" in the silicon-containing oxide coating or the silicon-containing oxide-coated aluminum nitride particles include the above-mentioned silica and composite oxides of silicon and aluminum. Examples of oxides include oxides, oxynitrides, oxycarbonitrides, etc. The silicon-containing oxide-coated aluminum nitride particles produced by the above-mentioned method for producing silicon-containing oxide-coated aluminum nitride particles maintain the high thermal conductivity of the aluminum nitride particles and have improved moisture resistance, so the heat-dissipating resin composition obtained by the method for producing a heat-dissipating resin composition of the present invention has excellent moisture resistance and thermal conductivity.

[0073] In the mixing step, the aluminum nitride particles coated with silicon-containing oxide produced by the above-mentioned method for producing aluminum nitride particles coated with silicon-containing oxide are mixed with a resin.

[0074] The resin to be mixed in the mixing step is not particularly limited, but is preferably a thermosetting resin, a thermoplastic resin, or a mixture of a thermosetting resin and a thermoplastic resin, in that the resulting heat dissipating resin composition has excellent heat resistance. Examples of the thermosetting resin include silicone resin, epoxy resin, phenol resin, bismaleimide resin, cyanate resin, urethane resin, (meth)acrylic resin, vinyl ester resin, unsaturated polyester resin, polyvinyl alcohol acetal resin, etc., and can be used alone or in combination of two or more kinds. Furthermore, a mixture of a thermosetting resin with a curing agent or a curing accelerator may be used. In particular, epoxy resin is preferable in terms of good heat resistance, adhesiveness, and electrical properties after curing, and silicone resin is preferable for applications in which flexibility and adhesion are important.

[0075] Silicone resins include addition reaction curing silicone resins, condensation reaction curing silicone resins, and organic peroxide curing silicone resins, and can be used alone or in combination of two or more types with different viscosities. In particular, when the obtained heat dissipating resin composition is used in an application that emphasizes soft adhesion, the silicone resin can be, for example, an addition reaction curing liquid silicone resin that does not generate by-products that can cause bubbles, and a silicone resin cured product can be obtained by reacting an organopolysiloxane having an alkenyl group as a base polymer with an organopolysiloxane having a Si-H group as a crosslinking agent at room temperature or by heating in the presence of a curing agent. Specific examples of the organopolysiloxane as a base polymer include those having a vinyl group, an allyl group, a propenyl group, a hexenyl group, etc. as an alkenyl group. In particular, a vinyl group is preferable as an organopolysiloxane. In addition, a platinum metal-based curing catalyst can be used as the curing catalyst, and the amount of addition can be adjusted to achieve the desired hardness of the resin cured product.

[0076] Examples of epoxy resins include bifunctional glycidyl ether type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, hydrogenated bisphenol A type epoxy resins, and biphenyl type epoxy resins; glycidyl ester type epoxy resins such as hexahydrophthalic acid glycidyl ester and dimer acid glycidyl ester; linear aliphatic epoxy resins such as epoxidized polybutadiene and epoxidized soybean oil; heterocyclic epoxy resins such as triglycidyl isocyanurate; and N,N,N',N'-tetraglycidyl-4,4' -diaminodiphenylmethane, N,N,N',N'-tetraglycidyl-1,3-benzenedi(methanamine), 4-(glycidyloxy)-N,N-diglycidylaniline, 3-(glycidyloxy)-N,N-diglycidylaniline and other glycidylamine type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, biphenyl aralkyl type epoxy resins, naphthalene aralkyl type epoxy resins, tetrafunctional naphthalene type epoxy resins, triphenylmethane type epoxy resins and other polyfunctional glycidyl ether type epoxy resins. The above-mentioned epoxy resins can be used alone or in combination of two or more kinds.

[0077] When the above-mentioned epoxy resin is used, a curing agent and a curing accelerator may be blended therein. Examples of the curing agent include alicyclic acid anhydrides such as methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and himic anhydride, aliphatic acid anhydrides such as dodecenylsuccinic anhydride, aromatic acid anhydrides such as phthalic anhydride and trimellitic anhydride, bisphenols such as bisphenol A, bisphenol F, and bisphenol S, phenol resins such as phenol-formaldehyde resin, phenol-aralkyl resin, naphthol-aralkyl resin, and phenol-dicyclopentadiene copolymer resin, and organic dihydrazides such as dicyandiamide and adipic acid dihydrazide. Examples of the curing catalyst include amines such as tris(dimethylaminomethyl)phenol, dimethylbenzylamine, 1,8-diazabicyclo(5,4,0)undecene and derivatives thereof, imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-phenylimidazole and derivatives thereof. These can be used alone or in combination of two or more kinds.

[0078] In the mixing step, in addition to the aluminum nitride particles coated with silicon-containing oxide, a filler that is usually used, such as boron nitride, alumina, silica, zinc oxide, etc., may be used in combination.

[0079] In the mixing step, the aluminum nitride particles coated with silicon-containing oxide and fillers other than the aluminum nitride particles coated with silicon-containing oxide may be mixed in amounts sufficient to provide a desired heat dissipating resin composition. The total content of the silicon-containing oxide-coated aluminum nitride particles and fillers other than the silicon-containing oxide-coated aluminum nitride particles in the obtained heat-dissipating resin composition is preferably 50% by volume or more and 95% by volume or less, more preferably 60% by volume or more and 90% by volume or less, and even more preferably 70% by volume or more and 90% by volume or less. If the total content is 50% by volume or more, good heat dissipation properties can be exhibited, and if it is 95% by volume or less, good workability can be obtained when using the heat-dissipating resin composition.

[0080] The content of the silicon-containing oxide-coated aluminum nitride particles in the obtained heat-dissipating resin composition is preferably 30% by volume or more and 100% by volume or less, more preferably 40% by volume or more and 100% by volume or less, and even more preferably 50% by volume or more and 100% by volume or less, of the total content of the silicon-containing oxide-coated aluminum nitride particles and fillers other than the silicon-containing oxide-coated aluminum nitride particles. A total content of 30% by volume or more can exhibit good heat dissipation properties.

[0081] In the mixing step, further, flexibility imparting agents such as silicone, urethane acrylate, butyral resin, acrylic rubber, diene rubber and copolymers thereof, silane coupling agents, titanium coupling agents, inorganic ion scavengers, pigments, dyes, diluents, solvents and the like can be appropriately added as necessary.

[0082] The mixing method in the mixing step is not particularly limited, and examples thereof include a method in which the silicon-containing oxide-coated aluminum nitride particles, resin, other additives, etc. are mixed, dissolved, and kneaded together or divided into portions using a dispersing / dissolving device such as a grinder, a planetary mixer, a rotation / revolution mixer, a kneader, or a roll mill, either alone or in appropriate combination, and heated as necessary.

[0083] The obtained heat dissipating resin composition can be formed into a sheet and reacted as necessary to form a heat dissipating sheet. The heat dissipating resin composition and heat dissipating sheet described above can be suitably used for bonding applications such as semiconductor power devices and power modules.

[0084] Examples of manufacturing methods for heat dissipation sheets include a method of molding a heat dissipation resin composition by a compression press or the like in a form in which both sides are sandwiched between substrate films, and a method of applying a heat dissipation resin composition onto a substrate film using a device such as a bar coater, screen printing, blade coater, die coater, or comma coater. Furthermore, the heat dissipation sheet after molding and application can be subjected to additional processing steps such as a process of removing the solvent, heating to bring the composition into a B-stage, or complete curing. As described above, various forms of heat dissipation sheets can be obtained by the process, making it possible to widely respond to the target fields of application and methods of use.

[0085] When applying or forming the heat dissipating resin composition on the substrate film, a solvent can be used to improve workability. The solvent is not particularly limited, but includes ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone, ether solvents such as 1,4-dioxane, tetrahydrofuran, and diglyme, glycol ether solvents such as methyl cellosolve, ethyl cellosolve, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, and diethylene glycol methyl ethyl ether, as well as benzyl alcohol, N-methylpyrrolidone, γ-butyrolactone, ethyl acetate, and N,N-dimethylformamide, which can be used alone or in combination.

[0086] In order to form the heat dissipating resin composition into a sheet, it is necessary to have sheet formability that maintains the sheet shape. In order to obtain sheet formability, a high molecular weight component can be added to the heat dissipating resin composition. For example, phenoxy resin, polyimide resin, polyamide resin, polycarbodiimide resin, cyanate ester resin, (meth)acrylic resin, polyester resin, polyethylene resin, polyethersulfone resin, polyetherimide resin, polyvinyl acetal resin, urethane resin, acrylic rubber, etc. can be mentioned. Among them, from the viewpoint of excellent heat resistance and film formability, phenoxy resin, polyimide resin, (meth)acrylic resin, acrylic rubber, cyanate ester resin, polycarbodiimide resin, etc. are preferable, and phenoxy resin, polyimide resin, (meth)acrylic resin, acrylic rubber are more preferable. They can be used alone or as a mixture or copolymer of two or more kinds.

[0087] The molecular weight of the high molecular weight component is preferably in the range of 10,000 to 100,000, more preferably 20,000 to 50,000.

[0088] The good sheet shape with good handleability can be maintained by adding a component having a weight average molecular weight in the above-mentioned range.

[0089] The amount of the high molecular weight component added is not particularly limited, but in order to maintain the sheet properties, it is preferably 0.1% by mass to 20% by mass, more preferably 1% by mass to 15% by mass, and even more preferably 2% by mass to 10% by mass, based on the heat dissipating resin composition. Note that an amount of 0.1% by mass to 20% by mass provides good handling and allows the formation of a good sheet or film.

[0090] The substrate film used in the manufacture of the heat dissipation sheet is not particularly limited as long as it can withstand the process conditions such as heating and drying during manufacture, and examples thereof include films made of polyesters having aromatic rings, such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polypropylene films, polyimide films, and polyetherimide films. The above-mentioned films may be multi-layer films combining two or more types, and may have a surface treated with a release agent such as a silicone-based release agent. The thickness of the substrate film is preferably 10 μm or more and 100 μm or less.

[0091] The thickness of the heat dissipation sheet formed on the base film is preferably 20 μm to 500 μm, more preferably 50 μm to 200 μm. When the thickness of the heat dissipation sheet is 20 μm or more, a heat dissipation sheet with a uniform composition can be obtained, and when the thickness is 500 μm or less, good heat dissipation properties can be obtained. EXAMPLES

[0092] The present invention will be specifically described below with reference to examples and comparative examples, but the scope of the present invention is not limited to these examples in any way. It should be noted that Example 17 should be read as a reference example.

[0093] [Specific surface area (m) of aluminum nitride particles determined by the BET method] 2 / g) for surface area of ​​1 m 2 Measurement of the amount of organic silicone compound coated per unit area The specific surface area (m2) of aluminum nitride particles determined by the BET method 2 / g) for surface area of ​​1 m 2 The coating amount of the organosilicone compound per unit area is calculated by the following formula: [mass (mg) of aluminum nitride particles coated with the organosilicone compound], [mass (mg) of aluminum nitride particles], and [specific surface area (m2) of aluminum nitride particles determined by the BET method, which is determined by the method described later]. 2 / g)] using the following formula (weight change method). The results are shown in the column "Coating amount of organic silicone compound" in the table. [Specific surface area (m) of aluminum nitride particles determined by the BET method] 2 / g) for surface area of ​​1 m 2 The amount of organic silicone compound coated per unit area (mg / m 2 )] = [Mass difference between aluminum nitride particles before and after coating with an organic silicone compound (mg)] / [Specific surface area of ​​aluminum nitride particles determined by the BET method (m 2 Surface area (m2) calculated from 2 )] (In the formula, [the difference in mass (mg) of the aluminum nitride particles before and after coating with the organosilicon compound] = [the mass (mg) of the aluminum nitride particles coated with the organosilicon compound] - [the mass (mg) of the aluminum nitride particles], [Specific surface area (m) of aluminum nitride particles determined by the BET method] 2 Surface area (m2) calculated from 2 )] = [specific surface area of ​​aluminum nitride particles obtained by the BET method (m 2 / g)] × [mass of aluminum nitride particles (g)].

[0094] [Measurement of carbon atom content in aluminum nitride particles coated with silicon-containing oxide] The carbon atom content of the aluminum nitride particles coated with silicon-containing oxide was measured by a carbon-sulfur analyzer (Carbon Anlyzer EMIA-821: manufactured by Horiba, Ltd.) using a non-dispersive infrared absorption method with a tubular electric furnace.

[0095] [Measurement of oxygen atom content in aluminum nitride particles coated with silicon-containing oxide] The oxygen atom content of the silicon-containing oxide-coated aluminum nitride particles was measured using an oxygen / nitrogen / hydrogen analyzer (ONH836: manufactured by LECO Japan LLC) after heating the silicon-containing oxide-coated aluminum nitride particles at 105°C for 2 hours in air.

[0096] [Measurement of silicon atom content of aluminum nitride particles coated with silicon-containing oxide] The silicon atom content of the aluminum nitride particles coated with silicon-containing oxide was measured by the following procedure. (1) Into a 20 cc Teflon (registered trademark) container, 10 cc of a solution prepared by mixing 97% by mass sulfuric acid (super grade, manufactured by Wako Pure Chemical Industries) and ion-exchanged water in a 1:2 (volume ratio) and 0.5 g of a sample (aluminum nitride particles coated with silicon-containing oxide) were placed. (2) The Teflon (registered trademark) container was placed into a stainless steel pressure vessel and maintained at 230°C for 15 hours to dissolve the placed sample. (3) The solution mixed in (1) was taken out, and the silicon atom concentration was measured using an ICP (Shimadzu Corporation, ICPS-7510) to calculate the silicon atom content of the aluminum nitride particles coated with silicon-containing oxide.

[0097] [Measurement of the coverage of silicon-containing oxide coatings on aluminum nitride particles by LEIS analysis] The coverage of the silicon-containing oxide film covering the surface of the aluminum nitride particles was determined by analysis using low energy ion scattering (LEIS) with an ion source and a rare gas as a probe. For LEIS, an IONTOF Qtac100 device was used. The incident ions were helium at 3 keV and 6 keV, and neon at 5 keV. The energy spectrum of the backscattered particles was obtained after oxygen cleaning. Based on the values ​​of the areas of the Al peaks of the aluminum nitride particles and the areas of the Al peaks of the aluminum nitride particles coated with silicon-containing oxide in the energy spectrum, the coverage of the silicon-containing oxide film covering the surface of the aluminum nitride particles was calculated by the following formula. (S Al (AlN)-S Al (AlN+SiO2)) / S Al (AlN) x 100(%) In the above formula, S Al (AlN) is the area of ​​the Al peak of the aluminum nitride particle, and S Al (AlN+SiO2) is the area of ​​the Al peak of the aluminum nitride particles coated with the silicon-containing oxide.

[0098] [Measurement of the specific surface area of ​​aluminum nitride particles determined by the BET method and the specific surface area x of aluminum nitride particles coated with silicon-containing oxide determined by the BET method] The specific surface area of ​​the aluminum nitride particles determined by the BET method and the specific surface area x of the aluminum nitride particles coated with silicon-containing oxide determined by the BET method were each measured using a Macsorb HM model-1210 manufactured by Mountech. A mixed gas of 70 volume % He and 30 volume % N2 was used as the adsorption gas. The specific surface area x determined by the BET method of the aluminum nitride particles coated with silicon-containing oxide is referred to as "BET specific surface area x (m 2 / g)" column.

[0099] [Measurement of Si / Al atomic ratio of aluminum nitride particles coated with silicon-containing oxide by AES analysis of the surface] The Si / Al atomic ratio of the surface of the aluminum nitride particles coated with silicon-containing oxide was measured by AES analysis using Auger electron spectroscopy in the following manner. The aluminum nitride particles coated with silicon-containing oxide were embedded and fixed in an indium foil using a hand press, and an Auger electron spectrometer (ULVAC-PHI, PHI-680) was used to measure the electron beam at an accelerating voltage of 2 kV and a current of 1 nA to obtain a spectrum. The spectrum was first differentiated and the peak heights of each element were used to determine the ratio of the number of Si atoms to the total number of Si atoms, O atoms, Al atoms, N atoms, and C atoms, and the ratio of the number of Al atoms to the total number of Si atoms, O atoms, Al atoms, N atoms, and C atoms. The Si / Al atomic ratio was further calculated from the ratio of the number of Si atoms to the total number of Si atoms, O atoms, Al atoms, N atoms, and C atoms, and the ratio of the number of Al atoms to the total number of Si atoms, O atoms, Al atoms, N atoms, and C atoms. The spectra were obtained at three points per field of view, for a total of 12 measurement points across four fields of view, and the average of the calculated Si / Al atomic ratios was taken as the "Si / Al atomic ratio measured by AES analysis of the surface of the aluminum nitride particles coated with silicon-containing oxide" and is shown in the "Si / Al atomic ratio by AES analysis" column in the table.

[0100] [Evaluation of particle moisture resistance] The moisture resistance of particles such as silicon-containing oxide-coated aluminum nitride particles was measured by putting 17 g of hydrochloric acid aqueous solution adjusted to pH 4 and 3 g of silicon-containing oxide-coated aluminum nitride particles into a 50 ml sample tube, sealing it, shaking it in a shaking thermostatic chamber at 60°C or 85°C, 80 rpm, and 2 hours, leaving it to stand, cooling it to room temperature (25°C), and measuring the ammonia concentration in the supernatant at a temperature of 25°C using an ammonia electrode (ammonia electrode 5002A: manufactured by Horiba, Ltd.). The results are shown in the "Moisture-resistant ammonia concentration" column in the table, along with the measurement temperature.

[0101] [Measurement of thermal conductivity of resin sheet (heat dissipation sheet)] The thermal diffusivity of the resin sheet was measured at 25°C using a laser flash thermal diffusivity measuring device (LFA447 NanoFlash: manufactured by NETZSCH). In addition, assuming that simple additivity holds for each component, the theoretical specific heat and theoretical density of the resin sheet were obtained by weighted averaging considering the amount of each component. The value calculated by multiplying the thermal diffusivity by the theoretical specific heat and theoretical density was taken as the thermal conductivity in the thickness direction of the resin sheet.

[0102] The samples for measuring thermal diffusivity were prepared by cutting the resin sheet to a size of 10 mm × 10 mm and a thickness of 300 μm, coating both sides with gold using an ion coater (IB-3: manufactured by EIKO Co., Ltd.), and then coating both sides with graphite.

[0103] The theoretical specific heat of the resin sheets in each of the Examples and Comparative Examples was calculated assuming that the theoretical specific heat of aluminum nitride is 0.73 J / g·K, that of the resin component is 1.80 J / g·K, and that of the high molecular weight component is 1.80 J / g·K. The theoretical density of the resin sheets in each of the Examples and Comparative Examples was calculated assuming that the theoretical density of aluminum nitride is 3.26 g / cm. 3 The theoretical density of the resin component is 1.17 g / cm 3 The theoretical density of the high molecular weight component is 1.17 g / cm 3 The calculation was made as follows: It was assumed that all the solvent had evaporated, and the amount of the hardener was so small that it was ignored.

[0104] [Particle preparation] Example 1 In the first step, the surface coating of aluminum nitride particles was carried out using a vacuum desiccator made of acrylic resin with a thickness of 20 mm, internal dimensions of 260 mm × 260 mm × 100 mm, and a structure divided into two levels, upper and lower, by a partition with through holes. 2 Approximately 30 g of aluminum nitride particles-A (JM: manufactured by Toyo Aluminum Co., Ltd.) with a molecular weight of 1000 / g was evenly spread on a stainless steel tray and allowed to stand. Next, 10 g of organosilicon compound-A (cyclic methylhydrogensiloxane tetramer: manufactured by Tokyo Chemical Industry Co., Ltd.), where n=4 in formula (3), was placed in a glass petri dish in the lower part of the vacuum desiccator and allowed to stand. Thereafter, the vacuum desiccator was closed and the mixture was heated in an oven at 80°C for 30 hours. The operation was performed while taking safety measures such as releasing hydrogen gas generated by the reaction through an open valve attached to the vacuum desiccator. After the first step was completed, the coating amount of the organosilicon compound containing the structure represented by formula (1) that coated the surface of the aluminum nitride particles was calculated from the specific surface area of ​​the aluminum nitride particles determined by the BET method, and the coating amount was determined based on the specific surface area per m2 of the surface area. 2 After the first step was completed, the sample was taken out of the desiccator and placed in an alumina crucible, and the sample was subjected to a heat treatment in the second step at 650°C for 1.5 hours in air, thereby obtaining silica-coated aluminum nitride particles as silicon-containing oxide-coated aluminum nitride particles.

[0105] Example 2 The aluminum nitride particles-A used as the raw material in Example 1 had a cumulative volume d50 of 16 μm and a specific surface area determined by the BET method of 0.5 m 2The aluminum nitride particles were prepared in the same manner as in Example 1, except that aluminum nitride particles-B (TFZ-N15P, manufactured by Toyo Aluminum Co., Ltd.) with a molecular weight of 1.001 g were used instead of aluminum nitride particles-B (TFZ-N15P, manufactured by Toyo Aluminum Co., Ltd.). After the first step was completed, the coating amount of the organosilicon compound having the structure represented by formula (1) that coated the aluminum nitride particle surface was calculated based on the specific surface area of ​​the aluminum nitride particles determined by the BET method. 2 The average dose was 0.70 mg per dose.

[0106] Example 3 The aluminum nitride particles-A used as the raw material in Example 1 had a cumulative volume d50 of 50 μm and a specific surface area determined by the BET method of 0.07 m 2 The aluminum nitride particles were prepared in the same manner as in Example 1, except that the aluminum nitride particles-C (FAN-f50-A1, manufactured by Furukawa Electronics Co., Ltd.) with a specific surface area of ​​1000 g / g were used instead. After the first step was completed, the coating amount of the organosilicon compound having the structure represented by formula (1) that coated the aluminum nitride particle surface was calculated based on the specific surface area of ​​the aluminum nitride particles determined by the BET method. 2 The average dose was 0.71 mg per dose.

[0107] Example 4 The preparation was carried out in the same manner as in Example 2, except that the organosilicon compound-A used as the raw material in Example 2 was replaced with organosilicon compound-B (product name LS-8150: manufactured by Shin-Etsu Chemical Co., Ltd.) in which R1 is a methyl group, R2 is hydrogen, and m is 1, as shown in formula (2). Note that the amount of the organosilicon compound containing the structure shown in formula (1) that coats the aluminum nitride particle surface after the first step is calculated based on the specific surface area of ​​the aluminum nitride particles determined by the BET method per m of surface area. 2 The average dose was 0.56 mg per dose.

[0108] Comparative Example 1 The raw materials and process conditions were the same as in Example 1, and the treatment up to the first step was carried out, but the heat treatment in the second step was not carried out. Note that the amount of the organic silicone compound containing the structure represented by formula (1) that coated the aluminum nitride particle surface after the first step was calculated based on the specific surface area of ​​the aluminum nitride particles obtained by the BET method, and was determined based on the specific surface area per m2 of the aluminum nitride particles.2 The average dose was 0.35 mg per dose.

[0109] Comparative Example 2 The aluminum nitride particles-B used as the raw material in Example 2, which were untreated and did not undergo any of the steps in the Example, were used as particles in Comparative Example 2.

[0110] Example 5 In the first step, the vacuum desiccator was closed and heated in an oven at 80°C for 30 hours. The procedure was the same as in Example 3, except that the desiccator was vibrated with a vibrator every hour, to produce silica-coated aluminum nitride particles as silicon-containing oxide-coated aluminum nitride particles.

[0111] Comparative Example 3 The aluminum nitride particles-C used as the raw material in Example 3, which were untreated and did not undergo any of the steps in Example 3, were used as the particles in Comparative Example 3.

[0112] Example 6 Silica-coated aluminum nitride particles were produced as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the first and second steps were further carried out in this order after the second step. The coating amount of the organosilicon compound after the first step and the coating amount of the organosilicon compound after the second step were both 0.65 mg / m 2 It was.

[0113] Example 7 The aluminum nitride particles-C used as the raw material in Example 3 had a cumulative volume d50 of 10 μm and a specific surface area calculated by the BET method of 1.1 m 2 Silica-coated aluminum nitride particles were prepared as the silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the aluminum nitride particles-D (TFZ-N10P: manufactured by Toyo Aluminum Co., Ltd.) were used instead of the silica-coated aluminum nitride particles-D (TFZ-N10P: manufactured by Toyo Aluminum Co., Ltd.).

[0114] Example 8 The aluminum nitride particles-C used as the raw material in Example 3 had a cumulative volume d50 of 30 μm and a specific surface area determined by the BET method of 0.11 m 2 Silica-coated aluminum nitride particles were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that aluminum nitride particles-E (FAN-f30-A1: manufactured by Furukawa Electronics Co., Ltd.) of 1000 g / g were used instead.

[0115] Example 9 The aluminum nitride particles-C used as the raw material in Example 3 had a cumulative volume d50 of 80 μm and a specific surface area determined by the BET method of 0.05 m 2 Silica-coated aluminum nitride particles were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that aluminum nitride particles-F (FAN-f80-A1: manufactured by Furukawa Electronics) of 1000 g / g were used instead.

[0116] Example 10 The aluminum nitride particles-C used as the raw material in Example 3 had a cumulative volume d50 of 1 μm and a specific surface area of ​​3.3 m as determined by the BET method. 2 Silica-coated aluminum nitride particles were prepared as the silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the silica-coated aluminum nitride particles were replaced with aluminum nitride particles-G (TFZ-N01P: manufactured by Toyo Aluminum Co., Ltd.) having a molecular weight of 1.0 to 1.0 g / g.

[0117] Example 11 Aluminum nitride particles coated with a composite oxide of silicon and aluminum were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the heat treatment conditions in the second step were 800°C and 3.0 hours.

[0118] Example 12 Aluminum nitride particles coated with a composite oxide of silicon and aluminum were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the heat treatment conditions in the second step were 800°C and 10.0 hours.

[0119] Example 13 Except for the conditions of the heat treatment in the second step being 800°C and 6.0 hours, and the first and second steps being further carried out in this order after the second step, aluminum nitride particles coated with a composite oxide of silicon and aluminum were produced as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 11. The coating amount of the organosilicone compound after the first first step and the coating amount of the organosilicone compound after the second first step were both 0.67 mg / m 2 It was.

[0120] Example 14 Aluminum nitride particles coated with a composite oxide of silicon and aluminum were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the heat treatment conditions in the second step were 850°C and 3.0 hours.

[0121] Example 15 Aluminum nitride particles coated with a composite oxide of silicon and aluminum were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the heat treatment conditions in the second step were 900°C and 3.0 hours.

[0122] (Example 16) Aluminum nitride particles coated with a composite oxide of silicon and aluminum were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the heat treatment conditions in the second step were 950°C and 3.0 hours.

[0123] Comparative Example 4 Aluminum nitride particles coated with a composite oxide of silicon and aluminum were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the heat treatment conditions in the second step were 1000°C and 3.0 hours.

[0124] Comparative Example 5 Aluminum nitride particles coated with a composite oxide of silicon and aluminum were prepared as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 3, except that the heat treatment conditions in the second step were 1100°C and 3.0 hours.

[0125] (Example 17) Silica-coated aluminum nitride particles were produced as silicon-containing oxide-coated aluminum nitride particles in the same manner as in Example 1, except that after the second step, the first step and the second step were further performed twice in this order. Note that the coating amount of the organosilicon compound after the first first step, the coating amount of the organosilicon compound after the second first step, and the coating amount of the organosilicon compound after the third first step were all 0.34 mg / m 2 It was.

[0126] [Manufacturing of resin sheets] Silicon-containing oxide-coated aluminum nitride particles of Examples 1 to 17 and Comparative Examples 1, 4 and 5, aluminum nitride particles of Comparative Examples 2 to 3, bisphenol A type epoxy resin (YD128: manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.) having an epoxy equivalent of 189 as a resin component, bisphenol A type phenoxy resin (YP50S: manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.) having a polystyrene equivalent weight average molecular weight of 40,000 as a high molecular weight component dissolved in 1-methoxy-2-propanol (solvent) at 30 mass%, and 2-ethyl-4-methylimidazole (2E4MZ: manufactured by Shikoku Chemical Industry Co., Ltd.) as a curing agent were mixed in the mass parts shown in Tables 1 to 4, and a resin sheet was obtained by the following procedure. The mixtures of the Examples and Comparative Examples were put into a planetary mixer and the mixture was adjusted under conditions of 2000 rpm and 30 seconds. Next, the mixtures of the Examples and Comparative Examples were made into a sheet of 450 μm thickness using a coater. After that, it was dried in a dryer at normal pressure of 60°C for 1 hour, and further dried under reduced pressure at 60°C for 10 minutes. The obtained sheet was then passed through a constant speed heat roll at a temperature of 90°C. In the constant speed heat roll, the sheet was passed through three gaps of 450μm, 400μm, and 350μm to make the sheet thickness uniform. Finally, in order to thermally cure the resin sheet, a heat press was used to perform heat compression molding under conditions of 10MPa, 120°C, and 30 minutes to obtain a cured resin sheet.

[0127] The particle content (volume %) of the resin sheets in the examples and comparative examples is calculated based on the theoretical density of aluminum nitride of 3.26 g / cm 3 The theoretical density of the resin component is 1.17 g / cm 3 The theoretical density of the high molecular weight component is 1.17 g / cm 3 The calculation was made assuming simple additivity for each component. The solvent was assumed to have completely evaporated, and the amount of hardener was ignored because it was in a small amount.

[0128] The aluminum nitride particles used and the silicon-containing oxide-coated aluminum nitride particles obtained in the examples and comparative examples were evaluated for the specific surface area (m2) of the aluminum nitride particles determined by the BET method. 2 / g) for surface area of ​​1 m 2The results of [measurement of the coating amount of organic silicone compound per unit area], [measurement of the carbon atom content of the silicon-containing oxide-coated aluminum nitride particles], [measurement of the oxygen atom content of the silicon-containing oxide-coated aluminum nitride particles], [measurement of the silicon atom content of the silicon-containing oxide-coated aluminum nitride particles], [measurement of the coverage rate of the silicon-containing oxide coating covering the surface of the aluminum nitride particles by LEIS analysis], [measurement of the specific surface area x of the silicon-containing oxide-coated aluminum nitride particles obtained by the BET method], [measurement of the Si / Al atomic ratio of the surface of the silicon-containing oxide-coated aluminum nitride particles measured by AES analysis], [evaluation of the moisture resistance of the particles], and [measurement of the thermal conductivity of the resin sheet (heat dissipation sheet)] are shown in Tables 1 to 4 and Figures 2 to 5. In addition, in the "Equations (4) and (5)" columns of Tables 1 to 4, if the equations (4) and (5) are satisfied, ◯ is indicated, and if the equations (4) and (5) are not satisfied, × is indicated.

[0129] These results show that Examples 1 to 17, which used aluminum nitride particles coated with silicon-containing oxide obtained by the method for producing aluminum nitride particles coated with silicon-containing oxide of the present invention, are able to maintain the high thermal conductivity of the aluminum nitride particles and significantly improve the moisture resistance of the aluminum nitride particles, compared to Comparative Examples 2 and 3, which were not subjected to the silicon-containing oxide coating treatment. Regarding the thermal conductivity, in particular, in Examples 2 and 4, the aluminum nitride particles of Comparative Example 2 were subjected to a silicon-containing oxide coating treatment, but the thermal conductivity of Examples 2 and 4 was nearly 90% of that of Comparative Example 2, which was not subjected to a silicon-containing oxide coating treatment. Also, in Examples 3, 5, and 6, the aluminum nitride particles of Comparative Example 3 were subjected to a silicon-containing oxide coating treatment, but the thermal conductivity of Examples 3, 5, and 6 was 95% or more of that of Comparative Example 3, which was not subjected to a silicon-containing oxide coating treatment. In the examples, the reason why good moisture resistance and high thermal conductivity were achieved at the same time is believed to be that an effective inorganic coating (silicon-containing oxide such as silica coating) was efficiently produced using a minimum amount of the organosilicon compound used for coating. Furthermore, in Example 6, in which the first and second steps were performed in sequence twice, the moisture resistance was improved and the thermal conductivity was almost unchanged compared to Example 3, which was the same except that the first and second steps were performed once. Moreover, Example 17, which does not satisfy formula (4), had a lower thermal conductivity than Example 1, which satisfies formulas (4) and (5).

[0130] On the other hand, in Comparative Example 1, which was treated up to the first step using the same raw materials and process conditions as in Example 1, but did not perform the heat treatment in the second step, the ammonia concentration was one order of magnitude worse than in Example 1. From this, it is considered that there is a close relationship between the moisture resistance and the carbon atom content of aluminum nitride particles coated with organosilicon. In other words, it can be inferred that the low carbon atom content is due to the change of the organosilicon compound coating to an inorganic silicon-containing oxide coating, and that the difference in the film quality of this coating significantly improved the moisture resistance. In the moisture resistance evaluation of Comparative Examples 2 and 3, the ammonia concentration was lower at 85°C, which is a harsher condition than 60°C, than at 60°C. This is presumably because, when a silicon-containing oxide coating is not formed, the hydrolysis reaction proceeds much faster at 85°C than at 60°C, and therefore an oxide coating is formed immediately after the particles are placed in the hydrochloric acid aqueous solution, making the hydrolysis reaction less likely to occur inside the oxide coating than at 60°C.

[0131] [Table 1]

[0132] [Table 2]

[0133] [Table 3]

[0134] [Table 4]

Claims

1. A silicon-containing oxide-coated aluminum nitride particle comprising an aluminum nitride particle and a silicon-containing oxide coating covering the surface of the aluminum nitride particle, The carbon atom content is less than 1000 ppm by mass, When the specific surface area of ​​the aluminum nitride particles coated with silicon-containing oxide, as determined by the BET method, is x (m 2 / g) and the content of silicon atoms in the aluminum nitride particles coated with silicon-containing oxide is y (ppm by mass), the following formula (4) is satisfied: The aluminum nitride particles coated with a silicon-containing oxide, when 3 g of the aluminum nitride particles coated with a silicon-containing oxide are immersed in 17 g of an aqueous hydrochloric acid solution adjusted to pH 4 at 85° C. for 2 hours, the concentration of ammonia extracted into the aqueous hydrochloric acid solution is 20 mg / L or less. y≦1000x+500 ... (4)

2. Silicon-containing oxide coated aluminum nitride particles as described in claim 1, wherein the concentration of the ammonia is 10 mg / L or less.

3. Silicon-containing oxide-coated aluminum nitride particles according to claim 1 or 2, which satisfy the following formula (5): y ≧ 100 ... (5)

4. 4. The aluminum nitride particles coated with silicon-containing oxide according to claim 1, wherein the carbon atom content is 50 ppm by mass or more.

Citation Information

Patent Citations

  • Method for making moisture-proof aluminum nitride powder and powder produced by this method

    JP1995507760A

  • Surface-treated aluminum nitride and its production

    JP2001019575A

  • Surface-modified particle

    JP2015071730A

  • Method for making moisture-proof aluminum nitride powder and powder produced by this method

    JP3446053B2

  • Aluminum nitride powder

    JP4088768B2